Customers’ Preferences for Crape Myrtle (Lagerstroemia L.) Across Geographical Regions: Evidence from China - Siwen Hao; Donglin Zhang; Yafeng Wen (Horticulturae)
Crape myrtle (Lagerstroemia L.), as a popular ornamental plant, holds significant importance in residents’ daily lives by supporting ecosystem services, enhancing urban aesthetics, and even impacting biological health. There are notable variations among crape myrtle species across different geographical distributions. However, potential differences in residents’ preferences for observing crape myrtle in various regions have not been thoroughly investigated. This study, based on a comprehensive analysis of 700 survey responses from diverse regions in China, sought to determine if discernible patterns exist in residents’ preferences for crape myrtle. The results revealed that residents across different regions exhibited distinct preferences for various ornamental characteristics of crape myrtle. These differences were particularly pronounced in intangible aspects such as cultural expression, ecological value, and economic value. Furthermore, the study demonstrated that the factors driving market demand for ornamental crape myrtle varied substantially across different regional populations. In north China, the flowering period and leaf size were identified as the primary factors influencing market interest. For south China, both the flowering period and flower size were crucial determinants. In central China, the key factors were the flowering period and flower color. The market demand in east China was largely driven by flower size and the flowering period. In northeast China, flower color and planting form played pivotal roles, while in northwest China, spatial ambiance and plant phenotype were significant in shaping preferences. Finally, in southwest China, landscape type and fruit color were the primary factors influencing market demand. These findings provide valuable insights into the relationship between regional preferences and the prevalence of crape myrtle, highlighting the potential factors that shape aesthetic choices in different parts of China.